Moisture absorbing film and mask comprising same
By using absorbent materials composed of water-soluble polymer, TPU and superabsorbent materials in the mask, the problems of moisture escape and fogging in the mask are solved, and higher airtightness and absorption performance are achieved.
Patent Information
- Application Number
- CN202380060739.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-03-28
AI Technical Summary
Existing masks cannot effectively prevent moisture from escaping, causing the wearer's glasses to fog, and it is difficult to prevent moisture from entering and exiting the edge of the mask, affecting airtightness.
An absorbent material consisting of water-soluble polymers, thermoplastic polyurethane (TPU) and superabsorbent material is used to absorb and retain moisture, thereby preventing moisture from escaping and reducing fogging on the glasses.
Through the use of absorbent materials, the moisture escape in the mask is significantly reduced, the glasses are prevented from fogging, and the airtightness and absorption performance of the mask are improved.
Smart Images

Figure CN119730820A_ABST
Abstract
Description
[0001] Cross-references to related patent applications
[0002] This application claims the benefit of and priority to U.S. Provisional Patent Application No. 63 / 400,649, filed on August 24, 2022, which is hereby incorporated by reference in its entirety for all intents and purposes. Technical Field
[0003] The present disclosure generally relates to absorbable materials and articles comprising absorbable materials. In particular, the present disclosure relates to polymer blends including superabsorbent materials. Background Art
[0004] Personal protective equipment, including face masks, is essential not only in research or hospital settings, but also for individuals who wish to protect their health. For example, a face mask worn by an individual in a public setting can protect the wearer from inhaling airborne particles, including dust, bacteria, harmful organisms, or other contaminants in the environment. A face mask can also provide protection for individuals in the vicinity of the wearer from respiratory droplets expelled when the wearer breathes or when the wearer talks, coughs, or sneezes.
[0005] An important aspect of a mask is to filter the breathable air from the environment. This may require that the mask be able to fit tightly against the wearer's face. In most cases, this may require that the mask be in direct contact with the area around the nose and mouth of the wearer's face. However, most masks do not form an airtight seal, so at least some air will flow in and out from the edges. If the mask wearer also wears goggles or corrective glasses, the exhaled air escaping from the mask upward toward the eyes may cause the glasses to fog up due to the moisture in the exhaled air. Glasses fogging may be exacerbated when the wearer engages in moderate or vigorous physical activities, such as walking, running, and sometimes even talking. Excessive fogging of glasses when wearing a mask may pose a safety hazard because continued fogging of the glasses can lead to poor vision and interfere with the wearer's actions to correct the fogging.
[0006] Manufacturers have been trying to solve the problem of glasses fogging by adding additional components to the mask, such as adding adhesive along the nose bridge portion of the mask to seal the gap between the nose and the mask. Since exhaled air is highly humid, adhesive along the nose bridge does not prevent glasses from fogging.
[0007] Therefore, there is a need for a mask and / or material for a mask that prevents moisture from escaping from the mask and prevents glasses from fogging. There is also a need or desire for a material with good absorption properties and reusability. Summary of the invention
[0008] The embodiments covered by the present disclosure are defined by the claims rather than by this Summary. This Summary is a high-level overview of various aspects of the invention and introduces some concepts that will be further described in the Detailed Description section below. This Summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used alone to determine the scope of the claimed subject matter. The subject matter should be understood by reference to the entire specification, some or all of the drawings, and appropriate portions of each claim.
[0009] In some embodiments, the present disclosure provides an absorbent material comprising a water-soluble polymer, a thermoplastic polyurethane (TPU), and a superabsorbent material. In some embodiments, the TPU comprises an aromatic group and an ester group. In some embodiments, the water-soluble polymer comprises a polyethylene oxide (PEO) having a weight average molecular weight (MW) greater than 50,000. In some embodiments, the superabsorbent material has an average particle size of 10 microns to 100 microns.
[0010] In an alternative embodiment, the present disclosure provides an article comprising: an absorbent material comprising: a thermoplastic elastomer; a thermoplastic elastomer having a weight average molecular weight (M) greater than 50,000; W ) of polyethylene oxide (PEO); and superabsorbent material. In some embodiments, the thermoplastic elastomer is a thermoplastic polyurethane (TPU). In some embodiments, the TPU comprises aromatic groups and ester groups. In some embodiments, the TPU comprises aromatic isocyanate monomers and polyester polyol monomers. In some embodiments, the PEO has an M greater than 150,000. W . In some embodiments, the absorbent material is a film. In some embodiments, the absorbent material is a foam. In some embodiments, the absorbent material comprises a film or a foam nonwoven laminate. In some embodiments, the absorbent article is a face mask. In some embodiments, the absorbent material is the outer layer of the face mask facing the user, and wherein the absorbent material is configured to directly or indirectly contact the user's skin. In some embodiments, the superabsorbent material has a particle size of 10 microns to 400 microns. In some embodiments, the film has a thickness of less than 500 microns. In some embodiments, the absorbent material exhibits an absorption capacity increase of at least 100% as measured by a dynamic vapor sorption test. In some embodiments, the article also includes a polyolefin-based adhesive for fixing the absorbent material to the article.
[0011] Other aspects, objects and advantages will become apparent through consideration of the detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figures 1A-1Cis a schematic illustration of the microstructure of an exemplary composition of absorbent material under expansion and contraction according to some embodiments described herein.
[0013] Figure 2 is a schematic diagram of a system for producing absorbent films according to some embodiments described herein.
[0014] Figure 3 is an illustration of a face mask comprising an absorbent material, according to some embodiments described herein.
[0015] Figure 4 is a graph of moisture absorption rates of exemplary film compositions at different relative humidity percentages according to some embodiments described herein.
[0016] Figure 5 is a graph of the change in mass percent of exemplary film compositions at different relative humidity percentages according to some embodiments described herein.
[0017] Figure 6 is a graph of moisture absorption rates of exemplary superabsorbent particles at different relative humidity percentages according to some embodiments described herein.
[0018] Figure 7 is a graph of the change in mass percent of exemplary superabsorbent particles at different relative humidity percentages according to some embodiments described herein.
[0019] Figure 8 is a graph of moisture absorption rate of superabsorbent particles according to some embodiments described herein. DETAILED DESCRIPTION
[0020] The present disclosure generally relates to absorbent materials, such as films, for masks and other articles. The absorbent materials and masks can be used to capture water vapor, thereby preventing the water vapor from condensing on a substrate near the mask. For example, the mask captures water vapor, such as the user's exhaled breath, and prevents the water vapor from leaving the mask and condensing on adjacent surfaces (such as, but not limited to, the user's glasses). Each example herein is given by way of illustration and is not meant to be limiting. For example, features illustrated or described as part of one embodiment or figure can be used in another embodiment or figure to produce yet another embodiment. It is intended that the present disclosure encompass such modifications and variations.
[0021] Definition and Description:
[0022] The terms "invention", "this invention" and "the present invention" as used herein are intended to refer generally to all subject matter of this patent application and the following claims. Statements containing these terms should be understood not to limit the subject matter described herein or to limit the meaning or scope of the following patent claims.
[0023] As used herein, the meaning of "a", "an" or "the" includes both singular and plural referents unless the context clearly indicates otherwise.
[0024] The term "film" herein refers to thermoplastic films produced using extrusion and / or forming processes such as cast film or blown film extrusion processes. This term includes apertured films, slit films, and other porous films that constitute liquid transfer films, as well as films that do not transfer fluids, such as, but not limited to, barrier films, filled films, breathable films, and oriented films.
[0025] The term "superabsorbent" herein refers to a water-swellable, water-insoluble organic or inorganic material that is capable of absorbing at least about 15 times its weight, and in one embodiment at least about 30 times its weight, in an aqueous solution containing 0.9 weight percent sodium chloride under most favorable conditions. Superabsorbent materials can be natural, synthetic, and modified natural polymers and materials. Additionally, superabsorbent materials can be inorganic materials such as silica gel or organic compounds such as cross-linked polymers.
[0026] The term "thermoplastic" refers herein to a material that is softenable and shapeable when exposed to heat and that substantially returns to a non-softened state when cooled.
[0027] The term "water-soluble" or "water-swellable" refers herein to materials that lose integrity over time in the presence of water.
[0028] Absorbent Materials
[0029] In various embodiments, the absorbent material described herein is a polymer composition in the form of a film or foam. The film or foam can repeatedly absorb and desorb moisture. The polymer composition is essentially a blend of a water-soluble polymer and an elastomeric thermoplastic polyurethane (TPU), and fine superabsorbent particles are dispersed throughout the blend. In some embodiments, the polymer composition may include one or more additional components. The polymer composition described herein is in the form of a film or foam, or the polymer composition may be used to produce a film or foam. The polymer blend acts as a bridge for transferring moisture from the environment to the absorbent material and then to the superabsorbent particles, which capture and retain moisture, thereby removing moisture from the environment.
[0030] Water-soluble or water-swellable polymers (ws)
[0031] The water-soluble (water-swellable) polymer that can be used for the absorbent material is not particularly limited, but should form a substantially homogeneous blend with the TPU. Examples of useful water-soluble polymers include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), polybutylene oxide (PBO), polyvinyl alcohol (PVA) and polyethylene glycol (PEG), hydroxypropyl cellulose, polyvinyl pyrrolidone, polyvinyl pyridine, gelatinized starch, nylon copolymers, polyacrylic acid, and mixtures thereof.
[0032] The WS polymer used in the absorbent material should allow moisture to enter the film. In some instances, the WS polymer may have a certain degree of crystallinity. In some instances, the WS polymer may have a degree of crystallinity of at least 40%, at least 50%, or at least 60%. The crystallinity of the WS polymer should be high enough so that the film has a degree of crystallinity of at least 25%. In some instances, the film has a degree of crystallinity of at least 25%, at least 35%, or at least 45%.
[0033] Any absorbent material described herein may include one or more water-soluble polymers. In some examples, the water-soluble polymer has a weight average molecular weight (MW) greater than 25,000, greater than 50,000, greater than 75,000, greater than 100,000, greater than 125,000, greater than 150,000, greater than 175,000, greater than 200,000, greater than 225,000, or greater than 250,000. w ). In some embodiments, the polymer composition comprises a ws polymer of an amount of about 10 wt % to about 90 wt % (e.g., 15 wt % to 85 wt %, 20 wt % to 80 wt %, 25 wt % to 75 wt %, 30 wt % to 70 wt %, 30 wt % to 65 wt %, 30 wt % to 70 wt %, 35 wt % to 65 wt % or 40 wt % to 60 wt %) based on the total weight of the composition. In some embodiments, the composition comprises at least 10 wt % (e.g., at least 15 wt %, at least 20 wt %, at least 25 wt %, at least 30 wt %, at least 35 wt %, at least 40 wt %, at least 45 wt %, at least 50 wt %, at least 55 wt %, at least 60 wt %, at least 65 wt % or at least 70 wt %) of a water-soluble polymer. In some instances, the ws polymer is PEO. In some examples, the PEO has a weight average molecular weight (MW) of greater than 25,000, greater than 50,000, greater than 75,000, greater than 100,000, greater than 125,000, greater than 150,000, greater than 175,000, greater than 200,000, greater than 225,000, or greater than 250,000. w ).
[0034] Elastomer Thermoplastic Polyurethane (TPU)
[0035] The TPUs useful in the absorbent materials described herein form substantially homogeneous blends with the ws polymers. In general, thermoplastic polyurethanes ("TPUs") are block copolymers consisting of alternating hard (i.e., crystalline) and soft (i.e., amorphous) segments or domains. The soft segments provide flexibility and elasticity, and the hard segments provide strength.
[0036] Thermoplastic polyurethanes are usually synthesized from diols (or polyols), organic diisocyanates and optional chain extenders. Polyols are usually any high molecular weight products with reactive active hydrogen components and contain substances with an average of about two or more hydroxyl groups per molecule. Usually, polyols are substantially linear and have two to three hydroxyl groups, and the number average molecular weight is 450 to 10,000, for example, 450 to about 6000, or 600 to 4500D. Short-chain diols provide harder, more crystalline polymer segments, and long-chain diols provide softer, more amorphous polymer segments. The chemical structure of the diols can also affect the properties of the polymer. For example, a TPU formed from a polyether-based diol can have different properties from a TPU formed from a polyester-based diol. The isocyanate selected for the TPU can also affect the properties of the polymer. For example, a TPU formed from an aromatic isocyanate can have different properties from a TPU formed from an aliphatic isocyanate.
[0037] TPU sometimes (but not always) contains a chain extender. Chain extenders typically have a number average molecular weight of about 60 to 400 and contain amino, thiol, carboxyl and / or hydroxyl functional groups. Examples of chain extenders include, but are not limited to, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, 1,4-cyclohexanediol, 1,4-dimethanol cyclohexane, and neopentyl glycol. In some embodiments, TPU may contain a chain extender. In some embodiments, the chain extender contains two to three hydroxyl groups.
[0038] By changing the ratio of diol to diisocyanate and the structure and molecular weight of each monomer, different TPUs can be synthesized. A variety of TPUs for the absorbent materials described herein have been studied, including polyurethanes based on aromatic polyesters (aromatic-ester TPUs), polyurethanes based on aromatic polyethers (aromatic-ether TPUs), polyurethanes based on aliphatic polyesters (aliphatic-ester TPUs), and polyurethanes based on aliphatic-polyethers (aliphatic-ether TPUs). Generally speaking, the aromatic or aliphatic segments of the TPU are derived from aromatic or aliphatic isocyanate monomers, and the polyester or polyether segments of the TPU are derived from polyester or polyether polyol monomers.
[0039] The properties of the film formed by the blend of ws polymer and aromatic-ester TPU are better than the properties of the film formed by the blend of ws polymer and aromatic-ether, aliphatic-ether or aliphatic-ester TPU. In the absorbent material described herein, the aromatic-ester TPU that can be used includes, but is not limited to, TPU whose polyester segments are derived from polyester diols and aromatic isocyanates. Examples of polyester diols include, but are not limited to, ethylene glycol polyadipate; 1,4-butanediol polyadipate; ethylene glycol-1,4-butanediol polyadipate; 1,6-hexanediol neopentyl glycol polyadipate; 1,6-hexanediol / 1,4-butanediol polyadipate; polycaprolactone; and mixtures thereof. Examples of aromatic diisocyanates include, but are not limited to, 2,4-toluene diisocyanate or 2,6-toluene diisocyanate; 4,4'-diphenylmethane diisocyanate; 2,4'-diphenylmethane diisocyanate; 2,2'-diphenylmethane diisocyanate; naphthalene-1,5-diisocyanate; xylene diisocyanate; methylene diphenyl isocyanate ("MDI"); hexamethylene diisocyanate ("HMDI"); and mixtures thereof.
[0040] Any absorbent material described herein may include one or more TPUs. In some embodiments, the TPU has a melting point of 75°C to 250°C, for example, 100°C to 240°C or 120°C to 220°C. The glass transition temperature (“T g ”) can be relatively low, for example, -150°C to 0°C, for example, -100°C to -10°C, -85°C to -20°C, or -60°C to -25°C. The melting temperature and glass transition temperature can be determined according to ASTM D-3417 was determined using differential scanning calorimetry ("DSC"). In some examples, the compositions described herein include TPU in an amount of 10% to 90% by weight (e.g., 15% to 85% by weight, 20% to 80% by weight, 25% to 75% by weight, 30% to 70% by weight, 30% to 65% by weight, 30% to 70% by weight, 35% to 65% by weight, or 40% to 60% by weight) based on the total weight of the composition. In some embodiments, the composition includes at least 10% by weight (e.g., at least 15% by weight, at least 20% by weight, at least 25% by weight, at least 30% by weight, at least 35% by weight, at least 40% by weight, at least 45% by weight, at least 50% by weight, at least 55% by weight, at least 60% by weight) of TPU.
[0041] Superabsorbent Material (SAM)
[0042] Absorbent materials also include superabsorbent materials (SAMs). Superabsorbent materials are generally used to increase the absorption capacity of a material. SAMs are present in the absorbent material in the form of fine particles or powders. Any type of SAM can be used, including natural, synthetic, and modified natural materials; inorganic materials (such as silica) or organic materials (such as chitin or starch); and biodegradable or non-biodegradable materials. Superabsorbent materials that can be used in the absorbent materials described herein include polymer powders, such as, but not limited to, various anionic, cationic, and non-ionic polymer materials. Suitable polymers include polyacrylamide, polyvinyl alcohol, ethylene maleic anhydride copolymers, polyvinyl ethers, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl morpholine, polyamines, polyethylene imine, polyquaternary ammonium, natural polysaccharide polymers (such as carboxymethyl cellulose, carboxymethyl starch, hydroxypropyl cellulose, alginic acid, alginates, carrageenan, acrylic acid grafted starch, acrylic acid grafted cellulose, chitin, chitosan) and synthetic polypeptides (such as polyaspartic acid, polyglutamic acid, polyasparagine, polyglutamine, polylysine and polyarginine) and salts, copolymers and mixtures of any of the foregoing polymers.
[0043] The superabsorbent particles in the absorbent material described herein should have an average particle size of about 10 microns to about 300 microns. In some instances, the average particle size of the superabsorbent particles is about 10 microns to about 50 microns (e.g., about 10 microns to about 40 microns, about 10 microns to about 30 microns, or about 10 microns to about 20 microns). For example, in an embodiment where the absorbent material is a film, the film can have a total thickness of about 100 microns. The superabsorbent particles must be less than the film thickness, and in order to obtain uniform dispersion and good function, the particles should be significantly less than the film thickness. For example, for a film with a thickness of about 100 microns, the superabsorbent particles can have an average particle size of up to about 15 microns, up to about 20 microns, or up to about 25 microns. In an embodiment where the film is thicker or the absorbent material is a foam, the average particle size of the superabsorbent material can be up to 50 microns, up to 100 microns, up to 200 microns, up to 300 microns, or up to 500 microns.
[0044] In some embodiments, the foam has a thickness greater than 300 microns (eg, greater than 350 microns, greater than 400 microns, greater than 350 microns, greater than 500 microns, or greater than 550 microns).
[0045] In addition to the above components, one or more other additives may be incorporated into the composition, such as plasticizers (e.g., sugars, sugar alcohols, polyols, urea, animal proteins, esters, combinations thereof and / or derivatives thereof), starch or its derivatives, lubricating additives (e.g., fatty acid salts, fatty acid amides, etc.), compatibilizers (e.g., functionalized polyolefins), dispersing aids, melt stabilizers, processing stabilizers, heat stabilizers, light stabilizers, antioxidants, heat aging stabilizers, brighteners, anti-sticking agents, binders, lubricants, fillers, etc.
[0046] Optionally, the absorbent material may further comprise a surface treatment agent to form a coating on the outermost surface of the material. The coating may provide beneficial properties without affecting the absorptive capacity of the film. For example, the surface coating may be an antimicrobial coating that provides an antimicrobial benefit to the user of the mask. A material is considered an antimicrobial material if it is effective in killing microorganisms. Examples of antimicrobial coatings include, but are not limited to, TiO2-containing coatings, SiO2-containing coatings, aromatic compound-containing coatings, or other coatings that contribute to an antimicrobial effect.
[0047] In some examples, the absorbent material described herein is a film or foam, wherein the blend of the ws polymer and the TPU is the first layer, and the foam or film further comprises one or more additional layers. For example, the additional layer may be an adhesive layer for fixing the film or foam to the outer layer of the mask or other article. Examples of suitable adhesive materials include hydrophobic and hydrophilic hot melt polymers, such as those obtained from Henkel (business address: Bridgewater, New Jersey, USA), such as 34-5610, 34-447A, 70-3998, and 33-2058; those obtained from Bostik-Findley (business address: Milwaukee, Wisconsin, USA), such as HX 4207-01, HX 2773-01, H2525A, H2800, H9574; and those obtained from HB Fuller Adhesives (business address: Saint Paul, Minnesota, USA), such as HL8151-XZP. Examples of other suitable adhesive materials include polyolefin-based adhesives, which have low tacky to non-tacky behavior, can resist creep, and can be non-toxic and recyclable.
[0048] The combination of water soluble polymer and TPU disclosed herein provides advantageous results. For example, the combination forms a substantially homogeneous blend, which is important for the water absorption properties of the material. If the WS polymer and TPU separate into different layers, absorption will be slow or even not occur at all. For example, if the polymers separate and the TPU is on the surface, the TPU will prevent moisture from reaching the superabsorbent particles, which will hinder the beneficial absorption level or even prevent any absorption.
[0049] The blend of ws polymer and TPU forms a matrix, and SAM particles are dispersed in the matrix. SAM particles are substantially uniformly dispersed in the polymer matrix. Uneven dispersion of SAM particles can have an adverse effect on the performance of the absorbent material. Without wishing to be bound by theory, it is believed that the hard segments of TPU interact most strongly with the crystalline segments of ws polymers, while the soft segments of TPU interact most strongly with the amorphous segments of ws polymers. The ws polymer provides a way for the film to capture water vapor and allow the water vapor to pass through the polymer blend to reach the superabsorbent material, where it is absorbed and retained.
[0050] During the capture and transfer of water to the SAM, the crystalline segments of the ws polymer dissolve to some extent, resulting in a conversion of the crystalline segments to a more amorphous structure. However, physical interactions with the hard segments of the TPU stabilize the ws polymer and prevent it from completely dissolving as the water is transferred through the membrane to the SAM. However, sufficient changes in the morphology of the crystalline regions can cause the fluffy absorbent material to swell. The extent of the swelling depends on the amount of water absorbed and the absorptive capacity of the SAM.
[0051] Absorption and swelling are reversible and repeatable. If the wet absorbent material is placed in a dry environment, the water will desorb. Sufficient water desorption will cause the material to shrink to its original state, after which it can absorb water again.
[0052] Figures 1A-1C is a schematic illustration of the microstructure of a polymer composition in one example of an absorbent material 100 as described herein. The polymer composition is depicted in three expansion / contraction stages, as shown in panels A, B, and C. In FIG1 , the absorbent material 100 comprises a water-soluble polymer 102, a TPU 106, and a SAM 104. In FIG1 , panel A shows the dry material, panel B shows the same material expanded after absorbing some water, and panel C shows the same material after absorbing additional water. The reverse desorption process is also depicted.
[0053] In some examples, the absorbent materials described herein can swell to up to a 100% increase in surface area, up to a 150% increase in surface area, or up to a 250% increase in surface area after being immersed in an aqueous liquid for three minutes.
[0054] When the absorbent material is a film, in some embodiments, the film can have a thickness of about 50 microns to about 400 microns (e.g., about 50 microns to about 200 microns, about 50 microns to about 100 microns, about 70 microns to about 150 microns, or about 90 microns to about 200 microns). In some embodiments, the film has a thickness of less than 400 microns (e.g., less than 350 microns, less than 300 microns, less than 250 microns, less than 200 microns, or less than 150 microns). In some embodiments, the film can have a width of about 5 mm to about 15 mm. In some embodiments, the film can have a length of about 50 mm to about 150 mm. The film is flexible and can be conformed to the article in which it is used.
[0055] Any known technology can be used to form the film described herein, including blow molding, casting, flat die extrusion, etc. In some embodiments, each component can be blended together to form a film using various known technologies. For example, the components can be supplied to a blending device individually or in combination. Before melt processing, the components can be dry mixed together to form a substantially homogeneous mixture of dry ingredients. Alternatively, the components can be supplied to a melt processing device (e.g., an extruder) that uniformly blends the materials simultaneously or sequentially.
[0056] Film can be prepared by batch or continuous processing technology.For example, mixer / kneader, Banbury mixer, Faro continuous mixer, single screw extruder, twin screw extruder, rolling mill etc. can be utilized to blend and melt process these materials.The example of suitable melt processing device includes co-rotating twin screw extruder (for example, the USALAB twin screw extruder of Thermo Electron Corporation of Stone, UK or the extruder of Werner-Pfreiderer of Ramsey, New Jersey).Such extruder can include feed and ventilation port and provide high intensity distributed and dispersed mixing.In any case, after extrusion, composition should be homogeneous.
[0057] The film composition described herein can be prepared by combining a water-soluble polymer with TPU and SAM particles, blending until the mixture reaches homogeneity, and extruding the mixture through a film die. In some instances, the TPU is provided in pellet form and the ws polymer is a dry powder. Optionally, the ratio of TPU to the ws polymer is about 1:2 to about 2:1. In some instances, the ratio of TPU to the ws polymer is about 1:1. In some instances, the polymer blend is extruded with a twin-screw extruder having a temperature distribution of about 200°F to about 450°F (e.g., about 300°F to about 350°F or about 300°F to about 400°F. In some instances, the polymer composition is heated to a temperature distribution of at least 100°F, at least 125°F, at least 150°F, at least 170°F, at least 180°F, or at least 190°F).
[0058] Figure 2 An exemplary system for producing a film according to some embodiments of the present invention is shown. Raw materials (e.g., water-soluble polymers, TPU, superabsorbent polymers, optional additives, etc.) are supplied to a melt blending device alone or as a blend. An extruder including one or more feed ports and vents may be used. Figure 2 The system 200 has two feed ports 230, 235 for adding the water-soluble polymer 210 and the TPU 220. Alternatively, however, the same port or different ports may be used to add the polymers simultaneously or sequentially. The system 200 uses a single screw extruder 240. Alternatively, however, the system may use any suitable extruder, such as a twin screw extruder. The polymer melt from the extruder 240 may be processed through a film die 250 to produce a film 280. As shown in FIG. Figure 2 As shown, system 200 includes a cooling roller 260 and a roller 270 for pulling and collecting the extruded film 280 downstream of the film die. Alternatively, however, the system can omit one or more rollers. In another example, TPU, ws polymer and SAP are pre-compounded and formed into pellets. Then, the pellets are used to extrude into films through a single screw extruder or a twin screw extruder.
[0059] Any known technology can be used to form foam as described herein. In some instances, water-soluble polymers, TPU and SAM particles are combined with solvents and foaming agents, and mixed to blend the polymers and evenly disperse the SAM particles. Any suitable foaming agent can be used, such as but not limited to sodium dodecyl sulfate (SDS) surfactant. The process produces a stable wet foam with high viscosity and consistency (some people describe it as similar to shaving cream). Optionally, the wet foam can be formed into any desired shape, such as a thin sheet. The wet foam is heated and dried to remove the solvent.
[0060] Articles containing absorbent material
[0061] In various embodiments, the absorbent materials described herein are combined with articles, such as articles of clothing or articles of protective equipment. For example, the absorbent material can be combined with a face mask. When combined with a face mask, the absorbent material can take the form of a film or foam and can be secured to the outer surface of the mask that faces the user. The absorbent material can cover the entire outer layer of the mask that faces the user, but it is not necessary to do so. In some instances, the absorbent material is a thin film and is secured to the top of the outer surface of the mask that faces the user. The film can be configured to contact the user's skin, such as skin near the bridge of the user's nose. In some embodiments, the film and mask fit the user's facial shape.
[0062] The absorbent material is capable of absorbing moisture expelled when the mask wearer exhales. The absorbent material can capture the exhaled moisture and prevent it from escaping from the mask, thereby preventing it from condensing and fogging on the wearer's glasses. Although the absorbent material is described as being used in a mask, a person skilled in the art will understand that the absorbent material can be used in a similar manner and for similar purposes for other articles. Therefore, the disclosure of masks is not intended to exclude other articles that can be combined with the absorbent material. A person skilled in the art will understand how to modify the present disclosure to use the absorbent material with other articles.
[0063] Figure 3 A mask 300 is shown according to one embodiment described herein. The mask 300 includes a body 302 formed of a filter material that can be used to filter harmful substances from the air breathed by the user. Alternatively, however, the body can be formed of any material that can be used for a mask, as determined by one skilled in the art. The body 302 can be configured to fit a portion of the user's face, such as above the user's mouth and nose. In some embodiments, as well as Figure 3 As shown, the mask 300 includes one or more straps 304, which can be used to keep the mask 300 in the appropriate position on the user's face. In some embodiments, the mask 300 has an outer surface 308 facing the user, which is opposite to the outer surface (not shown) facing the environment. The absorbent material 306 is shown as a thin strip at the top of the outer surface 308 facing the user of the mask 300. The absorbent material is set to contact the user's skin near the bridge of the user's nose. In an alternative embodiment, the absorbent material 306 can be positioned at the periphery of the mask 300 or any other suitable area, as determined by those skilled in the art. In an alternative embodiment, the absorbent film laminate can be prepared by using any nonwoven or porous material adhesive or heat laminated film. The laminate can then be attached to the product with adhesive, ultrasonic / pressure or any other similar bonding method.
[0064] Example
[0065] In the following examples, TPU-1 is an aromatic polyester TPU pellet with a trade name of WHT-F170 (Wanhua Chemical), and TPU-2 is an aromatic polyester TPU pellet with a trade name of 58238 TPU, from Lubrizol Advanced Materials, Inc. Cleveland, OH; PEO is a water-soluble polyethylene oxide powder, trade name Polyox WSR N80 (Dow Chemical); SAP is a superabsorbent powder, trade name Aqua Keep 10SH-NF (Sumitomo Chemical).
[0066] In order to evaluate the water absorption properties of the membranes according to the embodiments disclosed herein, the example membranes and comparative example membranes were produced from blends of TPU and PEO (with and without SAM). For each membrane, the dry membrane weight was measured and recorded. The membrane was then immersed in water or saline solution (0.9% NaCl) for 30 seconds, 60 seconds and 180 seconds, and the weight was re-evaluated. Table 1 provides the composition and weight of the membranes of Example 1 and Example 2 and Comparative Example 1.
[0067] Table 1
[0068]
[0069] The TPU / PEO-SAP film showed an absorption rate that quickly reached 200% within 30 seconds and reached a maximum absorption rate of up to 320% within 180 seconds. The film containing SAP showed better absorption behavior, especially in appearance. In addition, the film containing SAP can be reused after drying, with a weight loss of about 5% after three soaking-drying cycles. The film without SAP showed a weight loss of nearly 40%-50% after soaking for 180 seconds. This is believed to occur due to the dissolution of PEO in water. It is believed that the rapid water absorption is related to the increased surface area of the SAP fine particle size.
[0070] The dynamic water absorption rate and mass change of the film composition are determined at the desired relative humidity, temperature and exposure time using a dynamic vapor sorption (DVS) instrument (e.g., DVS Adventure system, from Surface Measurement Systems, LTD). In a typical experiment, a sample amount of 10 mg to 20 mg of the film composition is placed in a DVS Adventure sample pan, and the sample is then exposed to a dynamically flowing air stream with precisely controlled relative humidity for a desired exposure time.
[0071] Figure 4: is a graph of moisture absorption speed of an exemplary film composition at different relative humidity levels. The film composition comprises 20% by weight of superabsorbent particles, 30% by weight of PEO and 50% by weight of TPU. The film is exposed to different relative humidity conditions while being kept at a constant 35°C. When exposed to a relative humidity of 35%, the film exhibits a maximum absorption speed (dm / dt) of about 0.28%, and within the first 100 minutes of exposure, the speed drops to about 0. At a relative humidity of 76%, the film composition has a maximum moisture absorption speed (dm / dt) of about 0.6 (%), and within the first 100 minutes of exposure, moisture absorption drops to about 0. At a relative humidity of 92%, the film exhibits a maximum absorption speed (dm / dt) of about 0.80 (%), however, the higher relative humidity sample shows a slower decrease in absorption speed compared to the lower relative humidity exposure conditions. Before reaching a 0 dm / dt absorption speed, 92% relative humidity exposure requires about 350 minutes.
[0072] Figure 5 is a graph of the percent change in mass of an exemplary film composition at different relative humidity levels. The film composition comprises 20 wt % SAM, 30 wt % PEO, and 50 wt % TPU. The film was exposed to different relative humidity conditions while being kept at a constant 35°C. When exposed to 35% relative humidity, the film showed a mass change of less than 10%, with an increase in mass within the first 50 minutes of exposure. At 76% relative humidity, the film composition showed an increase in mass of about 17% within the first 50 minutes of exposure to the condition. When exposed to 92% relative humidity, the film composition experienced an increase in mass of more than 50%. A mass change occurred within 450 minutes when exposed to 92% humidity, and the mass increased exponentially within the first 200 minutes of exposure.
[0073] The results show that the film composition absorbed little moisture when exposed to low humidity conditions, but experienced greater moisture absorption when exposed to high humidity conditions. The results also show that the film's moisture absorption rate is rapid, with most absorption occurring within the first 50 minutes of exposure. Exhaled air has a relative humidity of nearly 100%, so the high moisture absorption capacity of the superabsorbent-containing film at high relative humidity can quickly remove large amounts of exhaled moisture when used in combination with a face mask. Thus, by quickly removing exhaled moisture before the exhaled air leaves the mask, the film can provide desirable anti-fogging properties.
[0074] While not wishing to be bound by theory, the increased water absorption rate and absorption capacity of the film compared to known products is attributed in part to the high surface area of the superabsorbent particles. To test this theory, we tested the superabsorbent particles using a separate dynamic vapor sorption (DVS) method. The water absorption rate of the superabsorbent particles was tested under different relative humidity conditions. Briefly, the superabsorbent particles were placed in an instrument, which was then exposed to a series of relative humidity changes and the change in mass over time was recorded. At each humidity change, the sample was allowed to first reach weight equilibrium before the next humidity change occurred.
[0075] Figure 6 is a graph of the moisture absorption rate of exemplary superabsorbent particles at different relative humidity levels.The superabsorbent particles described herein may be from about 10 microns to 300 microns. Figure 6 The size of the superabsorbent particles used in the experiments shown is 20 microns. The 20 micron superabsorbent particles were exposed to different relative humidity conditions and the weight change over time was measured. When the superabsorbent particles were exposed to a relative humidity of about 58%, the moisture absorption rate (dm / dt) was about 0.3 (%) within 20 minutes, and the absorption rate dropped to 0 within about 250 minutes. When the superabsorbent particles were exposed to a relative humidity of about 76%, they also showed a maximum absorption rate (dm / dt) of about 0.5% within the first 20 minutes, and the absorption rate dropped to about 0 within the first 250 minutes. When the superabsorbent particles were exposed to a relative humidity of about 92%, the maximum absorption rate (dm / dt) of about 1.2% was shown within the first 25 minutes. Under high humidity conditions (such as 92% relative humidity), the superabsorbent particles experienced moisture absorption after 400 minutes of exposure.
[0076] Figure 7 is a graph of the percent change in mass of exemplary superabsorbent particles at different relative humidity levels. The superabsorbent particles were exposed to different relative humidity conditions while being maintained at a constant 35°C. When exposed to 58% relative humidity, the superabsorbent particles showed a mass change of less than 40%, with an increase in mass within the first 250 minutes of exposure time. The film composition exposed to 76% relative humidity showed an increase in mass of about 65% within the first 450 minutes of exposure. When exposed to 92% relative humidity, the superabsorbent particles experienced a mass increase of more than 1200%. When exposed to 92% humidity, a mass change occurred within 450 minutes, and the mass increased exponentially within the first 200 minutes of exposure.
[0077] To demonstrate the advantages of superabsorbent fine particles used in films according to embodiments described herein, examples of these particles, SAP-1 (Aqua Keep 10SH-NF, Sumitomo Seika Chemicals Co., Japan), were compared with two commercial products, SAP-A (Evonik 5630, from Evonik Industries, with a particle size range of 300 microns to 600 microns) and SAP-B (SG200, from SDP Global / Sanyo Chemical, with a particle size range of 300 microns to 600 microns). Figure 8 As shown, compare the moisture absorption speed of SAP-1 (Example 1) and SAP-A and SAP-B (Comparative Example 1 and Comparative Example 2).SAP-1 particles (Example 1) show a maximum speed absorption of about 1.2 in the first 20 minutes, while Comparative Example 1 and Comparative Example 2 experience a maximum absorption speed of about 0.7 and 0.6 respectively.Compared with SAP-A and SAP-B (Comparative Example 1 and Comparative Example 2), the SAP-1 particles of Example 1 show a faster absorption speed.Although not bound by any theory, it may be due to the smaller size of superabsorbent particles described herein, so the surface area of these particles and liquid interaction is larger, thereby increasing their absorption speed shown.Very fine particles can also be coextruded with polymer blends, to form uniform functional moisture management films as described herein.
[0078] Example 2: Absorption properties of a mask adhered to a film
[0079] To test the effectiveness of the films described herein as a barrier along the nose of a mask, four films were prepared into 0.75" x 4.25" strips and each film was adhered to the top, user-facing outer surface of the mask. The films were secured to the mask using a polyolefin-based adhesive. The user then wore each mask for 1 to 3 hours. The results are shown in Table 2 below. Each user was required to wear the mask for normal daily activities, such as office work or walking. The weight of the film was measured before and after wearing.
[0080] Table 2
[0081]
[0082]
[0083] As can be seen from Table 2, after the user wears the mask, the weight of the film increases by 10% to 34%. When the user wears the mask with the moisture absorbing film, the fogging of the glasses is reduced, if not eliminated. It should be noted that, as shown in Figures 1-5, the absorption capacity of the film may be affected by the relative humidity in the room and the wearing time of the user. In some embodiments, the film may contain a higher percentage of SAP particles, which can increase the absorption capacity of the film. It can also be easily anticipated that the film with the desired size / shape / SAM loading can be placed in any desired area within the mask in direct contact with the skin, or as a built-in part of the inner layer within the mask structure, so as to avoid direct contact with the skin.
[0084] All patents, publications and abstracts cited above are incorporated herein by reference in their entirety. Various embodiments of the present invention have been described to achieve the various purposes of the present invention. It should be appreciated that these embodiments are merely to demonstrate the principles of the present invention. It will be apparent to those skilled in the art that various modifications and adjustments of the present invention will be apparent without departing from the spirit and scope of the present invention as defined in the following claims.
[0085] Although the present invention has been described in detail with respect to its specific embodiments, it will be appreciated that those skilled in the art can easily conceive of alternatives, variants and equivalents of these embodiments after obtaining an understanding of the foregoing. Therefore, the scope of the present invention should be assessed as the scope of the attached claims and any equivalents thereof and the following embodiments:
[0086] Embodiment 1: An absorbent material comprising a water-soluble (water-swellable) polymer, a thermoplastic polyurethane (TPU), and a superabsorbent material.
[0087] Embodiment 2: The absorbent material of any preceding or subsequent embodiment, wherein the TPU comprises aromatic groups and ester groups.
[0088] Embodiment 3: The absorbent material of any preceding or subsequent embodiment, wherein the water soluble polymer comprises polyethylene oxide (PEO) having a weight average molecular weight (MW) greater than 50,000.
[0089] Embodiment 4: The absorbent material of any preceding or subsequent embodiment, wherein the superabsorbent material has an average particle size of 10 microns to 100 microns.
[0090] Embodiment 5: An article, comprising: an absorbent material, the absorbent material comprising: a thermoplastic elastomer; a thermoplastic elastomer having a weight average molecular weight (M) greater than 50,000; W ) of polyethylene oxide (PEO); and superabsorbent material.
[0091] Embodiment 6: The article of any preceding or subsequent embodiment, wherein the thermoplastic elastomer is a thermoplastic polyurethane (TPU).
[0092] Embodiment 7: The article of any preceding or subsequent embodiment, wherein the TPU comprises aromatic groups and ester groups.
[0093] Embodiment 8: The article of any preceding or subsequent embodiment, wherein the TPU comprises aromatic isocyanate monomers and polyester polyol monomers.
[0094] Embodiment 9: The article of any preceding or subsequent embodiment, wherein the PEO has an M greater than 150,000. W .
[0095] Embodiment 10: The article of any preceding or subsequent embodiment, wherein the absorbent material is a film.
[0096] Embodiment 11: The article of any preceding or subsequent embodiment, wherein the absorbent material is a foam.
[0097] Embodiment 12: The article of any preceding or subsequent embodiment, wherein the absorbent material comprises a film or foam nonwoven laminate.
[0098] Embodiment 13: The article of any preceding or subsequent embodiment, wherein the absorbent article is a face mask.
[0099] Embodiment 14: The article of any preceding or subsequent embodiment, wherein the absorbent material is an outer layer of the mask that faces the user, and wherein the absorbent material is configured to directly or indirectly contact the user's skin.
[0100] Embodiment 15: The article of any preceding or subsequent embodiment, wherein the superabsorbent material has a particle size of 10 microns to 400 microns.
[0101] Embodiment 16: The article of any preceding or subsequent embodiment, wherein the film has a thickness of less than 500 microns.
[0102] Embodiment 17: The article of any preceding or subsequent embodiment, wherein the foam has a thickness greater than 300 microns.
[0103] Embodiment 18: The article of any preceding or subsequent embodiment, wherein the absorbent material exhibits at least a 100% increase in absorbent capacity as measured by the Dynamic Vapor Sorption Test.
[0104] Embodiment 19: The article of any preceding or subsequent embodiment, further comprising a polyolefin-based adhesive for securing the absorbent material to the article.
Claims
1. An absorbent material comprising a water-soluble (water-swellable) polymer, a thermoplastic polyurethane (TPU) and a superabsorbent material.
2. The absorbent material of claim 1, wherein the TPU comprises aromatic groups and ester groups.
3. The absorbent material of claim 1, wherein the water-soluble (water-swellable) polymer comprises a polymer having a weight average molecular weight (MW) greater than 50,000. W ) of polyethylene oxide (PEO).
4. The absorbent material of claim 1, wherein the superabsorbent material has an average particle size of 10 microns to 100 microns.
5. A product, comprising: An absorbent material, the absorbent material comprising: Thermoplastic elastomers; Having a weight average molecular weight (M) greater than 50,000 W ) of polyethylene oxide (PEO); and Super absorbent material.
6. The article of claim 5, wherein the thermoplastic elastomer is a thermoplastic polyurethane (TPU).
7. The article of claim 6, wherein the TPU comprises aromatic groups and ester groups.
8. The article of claim 6, wherein the TPU comprises aromatic isocyanate monomers and polyester polyol monomers.
9. The article of claim 5, wherein the PEO has an M greater than 150,000. W .
10. The article of claim 5, wherein the absorbent material is a film.
11. The article of claim 5, wherein the absorbent material is a foam.
12. The article of claim 5, wherein the absorbent material comprises a film or foam nonwoven laminate.
13. The article of claim 5, wherein the article is a face mask.
14. The article of claim 13, wherein the absorbent material is an outer layer of the mask that faces the user, and wherein the absorbent material is configured to directly or indirectly contact the user's skin.
15. The article of claim 5, wherein the superabsorbent material has a particle size of 10 microns to 400 microns.
16. The article of claim 10, wherein the film has a thickness of less than 400 microns.
17. The article of claim 11, wherein the foam has a thickness greater than 300 microns.
18. The article of claim 5, wherein the absorbent material exhibits at least a 100% increase in absorbent capacity as measured by the Dynamic Vapor Sorption Test.
19. The article of claim 5 further comprising a polyolefin-based adhesive for securing the absorbent material to the absorbent article.